BANK LENDING, ECONOMIC GROWTH AND THE PERFORMANCE OF THE MANUFACTURING SECTOR IN NIGERIA - Obamuyi, Tomola Marshal; Edun, Adebisi T.; Kayode, Olawale Femi (European Scientific Journal, ESJ, 2012)
The study investigates the effect of bank lending and economic growth on the manufacturing output in Nigeria. Times series data covering a period of 36 years (1973-2009) were employed and tested with the cointegration and vector error correction model (VECM) techniques. The findings of the study show that manufacturing capacity utilization and bank lending rates significantly affect manufacturing output in Nigeria. However, the relationship between manufacturing output and economic growth could not be established in the country. These results, therefore, call for concerted effort by the government, manufacturers and the lending institutions to reviewing the lending and growth policies and provide appropriate macroeconomic environment, in order to encourage investment-friendly lending and borrowing by the financial institutions.